134 - THE VIOLENCE AGAINST CHILDREN: A PUBLIC HEALTH PROBLEM? (Fiep Bulletin - online, 2011)
This study that aims to reflect on violence against children in Brazil, emphasizing the importance of the family and the public health in that context. Having said that, the violence against children is considered an unfair arguing between the adult abuser and child assaulted. In this perspective, it is for health professionals, especially those in nursing, because they are closer to the "family", to identify cases of violence and notify them; and this way, seek to understand the bio-psychosocial aspects of all people involved in that process.
Keywords: violence; care of the child; family; nursing